2020
DOI: 10.24251/hicss.2020.063
|View full text |Cite
|
Sign up to set email alerts
|

Building Bridges, Burning Bridges: The Use of Boundary Objects in Agile Distributed ISD Teams

Abstract: Boundary objects are physical and abstract artefacts which support team interactions across diverse knowledge domains. Despite their relevancy, research into the effectiveness of boundary objects in agile distributed ISD remains nascent. In this paper, we develop a framework to theorize their effectiveness in generating cohesion within distributed teams. Our indepth case study finds that their effectiveness is influenced by the nature of the boundary objects themselves but also by team members' willingness to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…For this purpose, we have reduced the number of research articles based on the selection criteria based on title, abstract, and introduction. Table 3 represents the selected articles using the tollgate approach [78], retrieved from the considered data repositories. 2) DATA EXTRACTION…”
Section: Figure 3 Tollgate Approach For Paper Selectionmentioning
confidence: 99%
“…For this purpose, we have reduced the number of research articles based on the selection criteria based on title, abstract, and introduction. Table 3 represents the selected articles using the tollgate approach [78], retrieved from the considered data repositories. 2) DATA EXTRACTION…”
Section: Figure 3 Tollgate Approach For Paper Selectionmentioning
confidence: 99%
“…Vahtera, et al [29] study of virtual teams found that identification with an 'in-group' can create negative perceptions of a perceived 'outgroup' which in turn intergroup interactions and brokerage between team members. The lack of a shared history and context can also make individuals unsure of their roles in the team, role expectations, and power relations [9,10,11]. In these situations, social identification occurs and is reinforced through individuals constructing a situational definition [cf.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, distributed teams are unlikely to have the shared context or shared history necessary to generate agreement early on due to their diverse professional, organisational, and disciplinary backgrounds [9,10,11]. This can create impediments during decision-making processes due to issues such as role ambiguity [12,13] and differences in interests [6,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a consistent understanding of values and principles, the agile manifesto was published 20 years ago [4]. It is known that social aspects like collaboration and communication are of importance in agile software development [5,6]. The iterative approach and recurring practices such as daily stand-up or planning meetings are characteristics of agile methods [7].…”
Section: Introductionmentioning
confidence: 99%